Price tagging the priceless: International reference pricing for medicines in theory and practice - Lisa Brandt (European Centre for International Political Economy (ECIPE), 2013)
International reference pricing (IRP) has become a popular policy instrument in Europe as government seeks to curb healthcare costs and notably reduce expenditure on medicines. IRP builds on systematic price comparisons with other countries and aims at fixing low reimbursement levels for drugs covered by the public health insurances. There are however serious concerns as to whether IRP is an adequate instrument in terms of reconciling the immediate need to reduce healthcare spending with the objective of fostering a dynamic and innovating atmosphere for future health technology improvements. Discussing the benefits and drawbacks of international reference pricing, this Policy Brief seeks to identify known effects and provide greater understanding of possible unintended consequences of IRP, particularly with respect to market distortions. Existing research shows that reference pricing may reduce drug prices and promote generic market entry in the short term. In the long run however, IRP risks causing negative dynamic effects. This is due to the fact that the operation of the price mechanism is set out of play. The IRP as an instrument is not designed to improve productivity and efficiency in the pharmaceutical market. Instead of basing prices on an assessment of the added therapeutic value of a new medicine, IRP focuses solely on cutting costs. As pharmaceutical companies react to policy incentives, launch delays have been observed as well as higher prices on branded drugs as firms try to compensate for foregone sales. Ultimately, by dampening the price competition and by discouraging incremental innovation, IRP may in the long run defeat its purpose and lead to increased medical expenses for the public healthcare sector.
Keywords: 330; Gesundheitskosten; Arzneimittel; Preisdifferenzierung; Preiswettbewerb; Wirkungsanalyse; EU-Staaten